Two polysaccharides from Porphyra modulate immune homeostasis by NF-κB-dependent immunocyte differentiation. Issue 4 (27th March 2019) - Fu, Linglin; Qian, Yi; Wang, Chong; Xie, Menghua; Huang, Jianjian; Wang, Yanbo
Abstract : Porphyra polysaccharides possess multiple pharmacological activities, such as immunoregulatory, anti-tumor and anti-inflammatory effects, but the specific underlying mechanisms are not fully understood. Abstract : Porphyra polysaccharides possess multiple pharmacological activities, such as immunoregulatory, anti-tumor and anti-inflammatory effects, but the specific underlying mechanisms are not fully understood. The present work was to investigate the immunomodulatory activity of two different Porphyra polysaccharides, PH and PY, in a BALB/c mouse model and a mouse splenic cell model. Results showed that PH and PY regulated Th1 and Th2 responses, which could be due to the proliferation of CD4 + CD25 + Treg. Further investigations demonstrated that PY induced the proliferation and maturation of upstream MHC II + CD11c + DC. Moreover, both PH and PY activate NF-κB signaling pathways in splenic cells, but the loss-of-function assay with a NF-κB inhibitor demonstrated that the direct Treg-induction activity of PH, but not PY, was mediated by NF-κB. These results suggested that PH and PY show strong immunomodulatory activity by NF-κB-dependent immunocyte maturation and differentiation, which facilitates further application of Porphyra polysaccharides as potential functional foods or immunomodulators.